Muzejní profese a veřejnost 2 Reflexe edukačního fenoménu v současné muzejní praxi - Holubová, Zuzana (Masaryk University Press, 2018)
Title in English: Museum professions and the public 2: Reflection of the educational phenomenon in contemporary museum practice. Among topical issues in present-day museology and museum practice is the dynamic relationship between science and education. The functionality of this interconnection in museum practice is projected into various forms of communication of research results achieved by professional museum workers to the general public. This mainly concerns the creation of well-understandable and visitor-attractive temporary and permanent exhibitions, specialised education programmes for schoolchildren or other groups, popularising thematic lectures and other accompanying programmes and cultural events, which at the same time observe the didactic rules of scientificity, presentiveness, interconnection of theory and practice etc. The publication offers a current insight into selected scientific disciplines involved in museum institutions and into the specifics of museum practice in the field of popularisation and mediation of their educational potential to the general public.